Postmortem toxicology - Skopp, Gisela (Forensic science, medicine, and pathology, 2010)
Results from toxicological analyses in death investigations are used to determine whether foreign substances were a cause of death, whether they contributed to death, or whether they caused impairment. Drug concentrations are likely to change during pre-terminal stages due to altered pharmacokinetics, to treatment during resuscitation or in the intensive care unit, to concomitant illness or to the presence of drug tolerance. The potential for postmortem changes must be considered in all but a few drugs. Formation of new entities as well as degradation of drugs may occur, especially in putrefied corpses; in addition, body fluids and tissues may be severely affected by autolysis and putrefaction. Specimens should be selected based on individual case history and on their availability. Analytical procedures should be performed in accordance with a proper quality assurance program for toxicological investigations. Problems are most likely to occur during the isolation and identification of a drug. Interpretation of analytical results is often limited by the inadequate information provided in a particular case.
Gesehen am 09.08.2023